Operationalscale application of entomopathogenic fungi for control of Sahelian grasshoppers - Kooyman, C.; Bateman, R.P.; Langewald, J.; Lomer, C.J.; Ouambama, Z.; Thomas, M.B. (1997)
Locusts and grasshoppers regularly threaten agricultural production across large parts of the developed and developing worlds. Recent concerns over the health and environmental impacts of standard chemical control measures have led to a demand for alternative, more environmentally benign control technologies. Here we present the results of a field study to investigate the potential of inundative biological control for control of grasshoppers in the Sahelian region of Africa. The biocontrol agent was an oil-based biopesticide formulation of a naturally occurring entomopathogenic fungus, Metarhiium flavoviride. This was applied at a rate of 21 ha−" to a total area of 150 ha using standard equipment normally used for the application of chemical pesticides. Twenty-one days after application, an 80% reduction in grasshopper populations was recorded in treated plots, relative to control populations in equivalent unsprayed areas. We think that this is the first operational-scale application of a biopesticide to demonstrate significant population reductions of key Sahelian grasshopper pests. This represents a substantial development in locust and grasshopper control, and should open the way for a new era of integrated control strategies where reliance on conventional chemicals is reduced.